Measurement of N+ flows in the high-field side scrape-off layer of ASDEX upgrade with different degrees of inner divertor detachment. (August 2017) - Karhunen, J.; Groth, M.; Heliste, P.; Pütterich, T.; Viezzer, E.; Carralero, D.; Coster, D.; Guimarais, L.; Hakola, A.; Nikolaeva, V.; Potzel, S.; ,
Highlights: Flows of injected N + ions have been measured in the HFS SOL of ASDEX Upgrade by Doppler spectroscopy in different degrees of HFS divertor detachment. Reversed flow was observed in the near SOL in high-recycling conditions, while the flow was in co-current direction across the SOL in detached conditions, suggesting re-distribution of SOL plasma pressure in detachment. Divertor plasma oscillations were found to increase parallel transport towards the HFS divertor. ERO simulations show entrainment below 50% between flow velocities of N + and D + ions. Abstract: Toroidal and poloidal flows of injected N + ions were measured in the high-field side (HFS) scrape-off layer (SOL) of ASDEX Upgrade by Doppler spectroscopy with different degrees of HFS divertor detachment. In high-recycling conditions, the results suggest reversed parallel N + flow away from the inner divertor in the near SOL close to the separatrix, while the flow is towards the inner divertor throughout the SOL in detached conditions. The measured poloidal N + flows were directed away from the HFS divertor in the near SOL for all density cases. Divertor plasma oscillations, characterized by momentary peaking of the HFS target ion flux and decrease of the HFS SOL density, were observed slightly before the roll-over of the ion saturation current to the HFS target and lead to an increase in the N + flow towards the HFS divertor. SOLPS and ERO simulations of the experiment predict entrainment below 50% between the velocities of N + and D + ions, suggesting that N + ions are quantitatively a limited proxy for measuring D + flows. ERO simulations show significantly higher entrainment for higher ionization states, e.g., N 2+ and N 3+ .